Simultaneous Determination of Paracetamol and Caffeine Content in Panadol® Caplet by UV-Vis Multicomponent Spectrophotometric Method - Tarigan, Astiara V.; Retno (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
Panadol® Extra caplet is a fixed-dose combination analgesic-antipyretic preparation containing paracetamol (500 mg) and caffeine (65 mg). Quantitative determination of both active pharmaceutical ingredients is essential to ensure pharmaceutical quality, efficacy, and patient safety. This study applied the UV-Vis multicomponent spectrophotometric method to simultaneously determine paracetamol and caffeine content in Panadol® Extra caplets and to elucidate how the chromophore-auxochrome electronic structure of each analyte governs its characteristic UV absorption behavior. Standard solutions of paracetamol BPFI and caffeine BPFI were prepared in 0.1 N HCl. Maximum absorption wavelengths were determined by scanning 200–400 nm. Absorptivity constants were obtained at λ₁ = 240 nm and λ₂ = 270 nm. Concentrations in the sample were resolved via simultaneous linear equations derived from Lambert-Beer’s law, and three independent preparations were evaluated statistically. The maximum absorption wavelengths were 240 nm for paracetamol and 270 nm for caffeine, consistent with their respective chromophore-auxochrome systems: paracetamol’s strong p–π resonance-amplified π→π* transition and caffeine’s moderate hyperconjugation-driven π→π* band. Paracetamol recovery ranged from 91.47% to 97.64% (mean 94.56 ± 1.33%), meeting the Farmakope Indonesia VI requirement of 90.0%–110.0%. Caffeine recovery ranged from 67.06% to 82.11% (mean 74.59 ± 3.23%), falling below the pharmacopoeial threshold due to the weaker auxochromic contribution of N-methyl groups and proportionally greater excipient matrix interference at the low working concentration. UV-Vis multicomponent spectrophotometry is valid and reproducible for paracetamol determination in this fixed-dose combination but requires method modification, such as UHPLC or second-derivative spectrophotometry, to achieve pharmacopoeial-compliant caffeine assay.